Gender Differences of Lower Extremity Amputation Risk in Patients With Diabetic Foot: A Meta-Analysis. (September 2014) - Tang, Zhu-Qi; Chen, Hong-Lin; Zhao, Fang-Fang
In this meta-analysis, we aim to evaluate gender differences of lower extremity amputation risk in patients with diabetic foot. Systematic computerized searches of PubMed and Web of Knowledge were performed. The pooled odds ratio (OR) and 95% confidence interval (CI) for amputation risk were calculated. Twenty studies with 15 385 case (present amputation) and 438 760 control (absent amputation) patients were included in the meta-analysis. The pooled crude OR was 1.676 (95% CI 1.307-2.149; Z = 4.07, P = .000). In the retrospective study subgroup, the pooled OR was 1.708 (95% CI = 1.235-2.363; Z = 3.24, P = .001); in the prospective study subgroup, the pooled OR was 1.478 (95% CI = 1.189-1.838; Z = 3.51, P = .000). The pooled adjusted OR was 1.439 (95% CI = 1.238-1.671; Z = 4.76, P = .000). In retrospective study subgroup, the pooled OR was 1.440 (95% CI = 1.208-1.717; Z = 4.07, P = .000); in prospective study subgroup, the pooled OR was 1.478 (95% CI = 1.080-2.024; Z = 2.44, P = .015). No significant publication bias was found. Sensitivity analyses by omitting a heterogeneity study showed the results were robust. In conclusion, our meta-analysis indicates that men with diabetic foot have about one half increased amputation risk than women with diabetic foot. Men with diabetes should receive more complete follow-up and more adequate health education.